Role of oral tramadol 50 mg in reducing pain associated with outpatient hysteroscopy: A randomised double‐blind placebo‐controlled trial. (February 2016) - Hassan, AbdelGany; Haggag, Hisham
Abstract : Background: Several drugs have been used to reduce hysteroscopy‐associated pain. Although the Royal College of Obstetricians and Gynaecologists has recommended against the use of opiates in outpatient hysteroscopy, we wished to investigate if opioids can be used if the appropriate opioid was given in the appropriate dose. Aim: To study the effectiveness of tramadol 50 mg in reducing pain associated with outpatient hysteroscopy. Materials and Methods: A prospective randomised double‐blind placebo‐controlled trial conducted in the outpatient hysteroscopy clinic at Cairo University Hospital. Main outcome measures were the severity of pain during the procedure, immediately after the procedure and 30 minutes later assessed by a visual analogue scale (VAS). VAS of 0 indicates no pain and VAS of 10 indicates the worst possible pain. Results: A total of 140 women who had diagnostic outpatient hysteroscopy were randomised to receive oral tramadol 50 mg or placebo one h before performing outpatient hysteroscopy. There was no difference between the groups in the age, parity, duration of the procedures or indications of hysteroscopy. The median pain score was significantly lower in the tramadol group during the procedure (5 vs 6; P = 0.013), immediately after the procedure (3 vs 4; P < 0.036), and 30 minute later (1 vs 2; P = 0.034). Two women in the tramadol group reported nausea, but this was mild and did not warrant cancelling the procedure. Conclusions: Oral administration of tramadol 50 mg before hysteroscopy reduces the pain evoked by the procedure and the drug was well tolerated by women.